Extraction and Characterization of Natural Dye Obtained from African Locust Bean (Parkia biglobosa) Pod Bark - Andema Aaron Kanadi; Joshua Yakubu; Kefas Wathagrda Shalbugau; Jamila Umar Atiku; James Yakubu; Peter Micheal Dass (Darul Yasin Al Sys, 2026)
Although natural dyes have attracted growing interest as sustainable alternatives to synthetic colorants, studies on the physicochemical, phytochemical, antimicrobial, and structural properties of dye extracts from African locust bean pod remain limited. This study investigated the extraction and characterization of a natural dye from African locust bean pod using the maceration method. The extraction yielded 23.76%, and the dye extract was dark brown, with a pH of 5.77, a melting point of 440 °C, a density of 0.54 g/mL, partial solubility in water, and complete solubility in methanol. Phytochemical screening revealed the presence of tannins, flavonoids, alkaloids, glycosides, phlabotannins, anthraquinones, quinones, terpenoids, steroids, carbohydrate, starch, proteins, and anthocyanins, while saponin was absent. The extract demonstrated antibacterial activity against B. subtilis, E. coli, S. aureus, P. aeruginosa, and S. typhi, and antifungal activity against P. notatum, but no antifungal activity was observed against C. albicans and A. niger at all concentrations. Characterization was conducted using UV-Vis, FTIR, GC-MS, HPLC, and SEM analyses. The UV-Vis spectrum showed distinct absorption peaks, with the highest absorbance recorded at 287 nm (4.1000), likely associated with carbonyl (C=O) groups characteristic of hydrolysable tannins. FTIR analysis indicated the presence of C–H stretching, C=C stretching, C=O stretching, and C–O stretching functional groups. GC-MS identified 19 compounds with varying retention times and peak areas, among which cis-9-hexadecenal (14.81%) was the major compound, followed by heneicosanoic acid (8.59%), hexadecanoic acid (7.93%), and octadecanoic acid (7.31%). HPLC analysis revealed gallic acid as the most abundant compound, indicating the presence of hydrolysable tannin, while SEM showed a rough and porous surface morphology with a compacted, fused-like solid structure. These findings demonstrate that African locust bean pod is a promising source of natural dye with notable bioactive and structural characteristics, thereby contributing to the growing body of knowledge on plant-based dye materials.